Moderation role of proactive coping between psychological place attachment and its mental health consequences in sojourners - Rida Muhammad Akbar; Muhammad Naveed Riaz (Journal of the Pakistan Medical Association, 2021)
Objective The study also examined the moderating impact of proactive coping strategies in the relationship of psychological place attachment and mental health related outcomes in sojourners. Methods The study was based upon self-report measures including Psychological Place Attachment Scale, Proactive Coping Inventory, Warwick Edinburg Mental Well-being Scale and Kasler Psychological Distress Scale. Total 300 sojourners participated in the study. Participants Academic sojourners are students who stay in a place for a limited period of time. Data of sojourners (N = 300) was collected from Sargodha using four self-report measures. Results Data analysis through PROCSS 3.2 revealed that Proactive coping, preventive coping and reflective coping were significantly moderated the relationship between affective and psychological distress. Proactive coping and reflective coping were significantly moderated the relationship between affective bonding and mental wells-being. Proactive coping preventive coping and avoidance coping significantly moderated the relationship home meaning and psychological distress. Proactive coping was moderated the relationship between home meaning and psychological distress. Proactive coping and reflective coping were moderated the relationship between place identity and psychological distress. Proactive coping was moderated the relationship between place identity and mental well-being. Instrumental support seeking was moderating the relationship between place dependence and psychological distress. Preventive coping and reflective coping were moderated the relationship between psychological place attachment and psychological distress. Reflective coping, strategic planning and preventive coping were significantly moderated the relationship between psychological place attachment and mental well-being. Continuous...